Combined Application of Organic Amendments and Gypsum to Reclaim Saline–Alkali Soil - Andrade Foronda, Demis; Colinet, Gilles (Agriculture (Basel), 2022)
Saline–alkali soils have high sodicity, high pH, and high levels of soluble salts, as well as carbonates. This study aimed to evaluate the effect of cattle manure and chicken manure combined with gypsum at three levels on reclaiming a saline–alkali soil, through a soil column experiment. Combined treatments were more effective than those of sole gypsum in reducing the initial exchangeable sodium percentage (ESP) below 5%. Electrical conductivity (ECe) was lowered below 1.6 dS m−1 by all treatments, except the control. The higher effectiveness of manures combined with gypsum can be explained by their synergistic effect on Na+ displacement and subsequent soil structure improvement, leading to an enhancement in the leaching process, and then the salinity/sodicity reduction. Soluble salts and Na+ were considerably reduced in all treatments at the first leaching. Soil ESP and ECe threshold values from the US Salinity Lab classification were reached by any treatment, except the control. The addition of cattle manure or chicken manure might enhance the reclamation effect of gypsum with leaching for some saline–alkali soils.